The Relationship between Peer Social Support and Homesickness Incidents in Overseas Students at the Faculty of Health Sciences, Muhammadiyah University, Jember - Eki Wulan Agustin; Mad Zaini; Komarudin (Cleanliness: Journal of Health Sciences and Medical Research, 2024)
Overseas students are students who are studying outside their area of ​​origin. Some overseas students tend to experience homesickness because they miss their parents and hometown, so they need support from their environment. Social support is information and feedback from other people that shows that someone is loved and cared for, appreciated and respected and is involved in a network of reciprocal communication and obligations. Quantitative research with a cross-sectional approach. The population in this study were overseas students at the Muhammadiyah University of Jember, Faculty of Health Sciences Class of 2023. The population in this study was 53 overseas students with a sample size of 47 people and was taken using simple random sampling techniques. The statistical test between peer support and the incidence of homesickness as measured using Spearman rho with α = 0.05 resulted in p value = 0.000, and r = -0.625, meaning that there is a relationship between social support from peers and the incidence of homesickness in overseas students. The suggestion of this research is that health institutions are advised to provide education related to social support from peers, especially overseas students, so that they are able to adapt to new environments.